An Overlap between Depression and Anxiety- A Literature Review - Patricia Wulandari (Scientia Psychiatrica, 2021)
Most studies show a high overlap between depression and anxiety syndromes. Relevant data come from representative studies. In clinical settings, the relative proportion of comorbid cases is even higher than that found in representative population surveys. Individuals with two concomitant disorders, suffering from a high overall burden, are more likely to seek treatment than individuals with only one disorder (Berkson’s paradox). Both depression and anxiety syndromes also co-occur with other psychiatric conditions such as substance abuse or personality disorders.